Recent topics in nonlinear PDE - Mimura, Masayasu; Nishida, Takaaki (Lecture notes in numerical and applied analysis ;, 1984)
This volume contains papers covering the theory of nonlinear PDEs and the related topics which have been recently developed in Japan.